(untitled) (Praxis Educativa, 2026)
The objective of this study was to design an inventory for teacher use to assess soft skills in secondary school students. The process included validation by expert judgment, a pilot test with 25 questionnaires, and adaptation. Subsequently, a non-probability sample was applied to 420 students (47% female, 53% male) between the ages of 12 and 19 (ME = 14.92; SD = 1.81). Initially, a parallel analysis suggested a four-factor structure of the IHBE. Exploratory factor analysis identified items with psychometric complexity, so 16 items were retained. The 16-item version measures four factors: interpersonal, social, intellectual, and accuracy skills. Semi-confirmatory factor analysis yielded goodness-of-fit indices (GFI = .98, AGFI = .96, RMSA = .000) with a 95% confidence interval. The IHBE showed high internal consistency (α = .97, .95, .85, and .90 for each factor; 97 for the total instrument). The results of the theoretical model support the validity and reliability of the preliminary version of the IHBE.